A Review of the Value of D-dimer Testing for Prediction of Recurrent Venous Thromboembolism with Increasing Age - Lippi, Giuseppe; Favaloro, Emmanuel J.; Cervellin, Gianfranco (Seminars in Thrombosis and Hemostasis, 2014)
Recurrent thrombosis is a relatively frequent complication of venous thromboembolism (VTE) and represents an important cause of clinical and economic issues for health care systems worldwide. Rates of thrombosis increase with increasing age, with aging recognized to be a risk factor for thrombosis. Although D-dimer is now regarded as the biochemical gold standard for assisting the diagnosis of VTE and predicting the recurrent risk of thrombosis, the interpretation of D-dimer values with increasing age remains challenging due to many factors. These include the development of age-related changes in both the microcirculation and blood coagulation, which ultimately contribute to generate a hypercoagulable state and a gradual increase of D-dimer concentration with aging. Convincing evidence has now been provided that while D-dimer values may be effectively utilized for predicting the risk of recurrent thrombosis with increasing age, conventional cutoff values are inappropriate for older populations. In summary, analysis of the current scientific literature suggests that the adoption of age-dependent thresholds may increase the diagnostic effectiveness of this biomarker with increasing age.
Keywords: D-dimer; venous thromboembolism; thrombosis; older people; aging